How Government Spending Priorities Breaks the Poverty Cycle: Evidence from East Indonesia - Arfanita, Andi; Nursini, Nursini; Adya Utami, Syukri (Jurnal Ekonomika : INDEPENDEN, 2025)
This study aims to evaluate the effectiveness of fiscal policy in reducing poverty in Eastern Indonesia, both directly and indirectly through health and education spending and economic growth. In this context, fiscal policy is measured through local own-source revenue, transfer funds, and regional borrowing, used for funding the health and education spending. Meanwhile, the dependent variable will be proxied by the percentage of poor people (P0). Pandemic will also included in the analysis as control variable. Regression with the Three-Stage Least Square (3SLS) method will be employed in this study, incorporating twelve provinces from 2010 to 2023, with a fixed effect model estimation. After conducting robustness checks, this paper reveals that regional incomes, measured by local own-source revenue, transfer funds, and government borrowing have significantly affected poverty, either directly or indirectly through education and health spending and economic growth channel. It means that those variables can play a significant role in mitigating poverty in Eastern Indonesia. Therefore, policies aimed at enhancing regional income, optimizing fund transfer, and prioritizing the allocation of expenditures and borrowing on developments that broadly benefit the Poor, are crucial for accelerating poverty reduction in Eastern Indonesia.